A bark of its own kind – the acoustics of 'annoying' dog barks suggests a specific attention-evoking effect for humans. Issue 2 (3rd March 2020) - Jégh-Czinege, Nikolett; Faragó, Tamás; Pongrácz, Péter
ABSTRACT: Dog barks represent a major source of noise pollution worldwide. However, the exact reasons why dog barks annoy people and why particular people show stronger reactions to dog barks than other noises, are poorly understood. In a sound playback study, we tested Hungarian participants ( N =  153) from three age groups and three residential areas. Each participant was tested with 12 different bark sequences, assembled from original barks, based on their pitch, inter-bark intervals and tonality. Subjects rated each sequence according to the degree of annoyance caused by the barks and also to the apparent inner state of the dog. The results showed that the residential area did not have an effect on annoyance ratings. However, compared to children and older adults, young adults found high-pitched barks to be the most annoying. This finding is consistent with earlier results of the effects of baby cries on humans. The most annoying barks showed unique acoustical structures (high pitch, low tonality), this combination was not associated with the extremities of any other emotional scales. We assume that the strong attention eliciting effect of particular barks could be one of the evolutionary reasons why barking has become the main vocalization of the dog during domestication.